Experiences of women with breast cancer receiving chemotherapy: A qualitative study - Dural, Gül (My University, 2024)
Aim: This study was conducted to determine the experiences of women with breast cancer who were receiving chemotherapy. Methods: The study was conducted with 15 women with breast cancer who were receiving chemotheraphy treatment in eastern Türkiye between December 2022 and April 2023, by using a qualitative descriptive design. Two forms were created by the researcher according to the purpose of the research and the population. The first form contains information of the participants, and the second form includes semi-structured interview questions. Inductive thematic analysis was used to evaluate the data. Ethics committee approval was obtained. Results: Mean age of the women in the study was 47.26 ± 10.21. It was found that 53% of the women were university graduates, 93% were married, 67% were unemployed, 73% had average level of income, 66% had no comorbid chronic disease and 53% had stage two cancer. As a result of the thematic analysis, five themes and sixteen sub-themes were determined: The themes were; (1) Receiving the first diagnosis (2) Emotional experiences, (3) Changes in life, (4) Symptom management, (5) Sources of information during treatment. Conclusion: It was found that receiving chemotherapy treatment created many problems, especially physical and emotional, in women with breast cancer. However, the women continued their treatment without giving up. The steps to be taken to define and understand these problems well will play an active role in women’s coping with the disease effectively.
Keywords: Breast cancer; chemotherapy; experience